PENGARUH INTENSITAS MODAL DAN CEO POWER TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2020-2023 - Tsani, Kharisma Amalia; Winedar, Mustika (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Tax avoidance remains a strategic issue in corporate financial management, particularly in industries with high public scrutiny, such as food and beverage manufacturing. This study analyzes the influence of capital intensity and CEO power on tax avoidance among companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. Methods: This research used a quantitative approach to collect secondary data from 84 firm-year observations selected through purposive sampling. The analytical method employed was multiple linear regression supported by descriptive and correlation analysis.Results: The results showed that both capital intensity and CEO power had no significant effect on tax avoidance (F = 0.225, p = 0.799). The adjusted R-squared value was −0.019, indicating that the model had very low explanatory power. The correlation between CEO power and capital intensity was −0.097, suggesting a weak and negative relationship. These findings imply that other factors, such as profitability, leverage, or corporate governance, may play a more substantial role in influencing tax avoidance. Therefore, further studies are recommended to explore these alternative determinants within different industrial contexts. Keywords: CEO Power, Capital Intensity, Tax Avoidance